Traditional Nevzine Dessert Production - Nuran Erdem (Turkish Journal of Agriculture: Food Science and Technology, 2020)
Traditional foods, which are the special products that have emerged with the experience of many years, reflect the culture, identity, characteristics and heritage of a region and help the development and continuity of these regions by preventing migration from rural areas. In terms of revealing the cultural richness of societies, the place of traditional foods in social life is very important. Traditional foods have an important place in the nutrition of the people living in the region and constitute the specific taste of the region. One of the cultural riches traditional desserts are produced and consumed in various regions of Anatolia. The desserts, which have been produced for centuries from past to present, have always had an important place in our culture. Traditional desserts have a rich variety both as milky and sherbet dessert in terms of the material added and the production technology. Nevzine Dessert, which has been produced for centuries, is a traditional sherbet dessert variety prepared by using tahini, molasses and walnuts of Kayseri province. The use of sugar and grape molasses in the sherbet is a feature that distinguishes this dessert from other syruped desserts. Nevzine Dessert is served on religious holidays and its energy is quite high.The aim of this study is to give information about Kayseri’s traditional Nevzine Dessert, its components, preparation and cooking based on the interviews and researches with the locals.